Determination Profitability of Islamic Banks with Exchange Rate as Moderating Variable - Budhi Pribadhi Ishak (Journal of Islamic Economics and Social Science (JIESS), 2021)
This study aims to analyze the factors that can affect Islamic banks' return on assets (ROA) in Indonesia. These factors include independent variables consisting of the ratio of operating costs to operating income (BOPO), Financing to Deposit Ratio (FDR), the ratio of financing income to total income, which is moderated by the exchange rate, the ratio of securities income to total income which moderated by the exchange rate, and also the exchange rate. The method used to analyze the determination of ROA is regression analysis with Error Correction Models (ECM). The research sample used is the entire research population, namely monthly data in 2016-2020 of Islamic Bank, including in the group of BUKU II published by the Financial Services Authority (OJK) and Bank Indonesia (BI). Therefore, the number of data observations in this study is 60 (sixty) data. The results of this study indicate that the long-term analysis: (i) BOPO has a negative and significant effect on ROA; (ii) FDR has no significant effect on ROA; (iii) The ratio of financing distribution moderated by the exchange rate has a positive and significant effect on ROA; (iv) Securities income ratio moderated by exchange rate has a negative and significant effect on ROA; (v) Exchange rate has a negative and significant effect on ROA.Meanwhile, for the short term are: FDR does not affect ROA. Furthermore, the results of the study for short-term analysis: (i) BOPO has a negative and significant effect on ROA; (ii) FDR has no significant effect on ROA; (iii) The ratio of financing distribution moderated by the exchange rate has a positive and significant effect on ROA; (iv) Securities income ratio moderated by exchange rate has no significant effect on ROA; (v) Exchange rate has a negative and significant effect on ROA. The implication of this research is to provide input and repertoire of knowledge for academics and practitioners related to the factors that affect the performance of Islamic banks (ROA). Therefore, based on this research, Islamic banks BUKU II to maintain their financial performance, Islamic banks must be able to develop financing products that are following the expectation and needs of the community. The originality of this study is to analyze the determination of ROA moderated by macroeconomic variables (ROA)